Examining Students' Attitudes Towards iPads as Interactive Multimedia Tools and their Impact on Learning Quality in Indonesian Private Secondary School - Mahnun, Nunu; Subaidi, Subaidi; Arsyad, Junaidi; Faruq, Umar (STAI Hubbulwathan Duri, 2024)
This study explores students' attitudes toward using iPads as interactive multimedia tools in learning Islamic education (PAI) and examines the impact of this approach on learning quality. With the growing integration of technology in education, understanding the effects of interactive multimedia like iPads on students' learning experiences is critical. A mixed-methods approach was employed, involving both quantitative and qualitative analysis. A sample of 123 students from grades 7 to 9 was selected through stratified random sampling from a school that uses iPads in its learning system. Additionally, ten students were purposively chosen for interviews based on varying levels of iPad engagement. Quantitative data were analyzed using descriptive statistics and regression analysis, while qualitative data were analyzed thematically. The findings indicated that students generally had a positive attitude toward using iPads in PAI learning. In both quantitative and qualitative assessments, students described the iPad-based learning as